Trade union ordinance 1959: the study of the power of the minister of labour and manpower under the act / Anuar Itam - Itam, Anuar (Faculty of Law, 1987)
It has been often said that freedom to associate is one of the pillas of a democratic society. Only by associating with one another, through trade un1ons, can the ordinary workers expect to have their views duly respected by the employers well as to secured from caprivous actions on the part of the employer. The Trade Union Ordinance, 1959 is the statute which provides for the regulation of trade unions. There can be no denying that regulation necessarily entails restrictions on the freedom in question. The project paper is concerned with the Trade Unions Ordinance, 1959 and the powers imposed upon the Minister, which powers are intended to ensure proper regulation of trade unions in the country. The rationale behind the powers conferred to this authority and the limitations on the powers are also discussed in this paper.